Behavioral and Environmental Risk Factors of Typhoid Fever: A Case-Control Study in Balongpanggang, Gresik Regency - Zamli, Zamli; Amanah, Indra; Alim, Andi; Yenni, Yenni; Rosita, Rosita (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Typhoid fever remains a significant public health burden in developing countries, including Indonesia, where poor hygiene and sanitation contribute to its endemicity. This study aimed to identify behavioral risk factors associated with typhoid fever in the working area of UPT Puskesmas Balongpanggang, Gresik Regency. A quantitative, analytic case control study was conducted involving 74 respondents, equally divided between the case group (patients diagnosed with typhoid fever) and the control group (individuals without the disease). Purposive sampling was applied to select participants, and data collection was carried out through structured interviews using a validated questionnaire. Statistical analysis was performed using chi square tests to evaluate associations between specific behaviors and disease occurrence. The study identified six significant behavioral risk factors: eating outside the home (OR = 5.022; 95% CI: 1.465–17.217), consuming raw food (OR = 15.231; 95% CI: 1.850–125.420), drinking untreated water (OR = 10.828; 95% CI: 3.182–36.848), poor knowledge about typhoid (OR = 90.417; 95% CI: 16.991–481.135), family history of typhoid (OR = 4.758; 95% CI: 1.720–13.164), and not washing hands after defecation (OR = 36.458; 95% CI: 7.491–177.444). These results emphasize the role of individual hygiene practices and household behaviors in typhoid transmission. In conclusion, this study provides strong evidence for prioritizing behavior focused public health interventions and educational programs as key strategies for typhoid fever prevention in endemic communities.